2011
DOI: 10.1021/je101288g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lactose and Ethanol Diffusion Coefficients in Calcium Alginate Gel Spheres: Predicting Values To Be Used in Immobilized Bioreactors

Abstract: The diffusion coefficients (D) for lactose and ethanol through calcium alginate gel beads were determined based on the mathematical approach of Fick's second law. Different experimental conditions were tested to evaluate the behavior of the diffusion coefficient of different concentrations of lactose and ethanol in Ca-alginate (3, 4, and 6) % at varying temperatures (298.15, 303.15, and 308.15) K. Results showed that diffusion coefficients were independent from the concentration of lactose and ethanol, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
2
14
0
3
Order By: Relevance
“…Earlier work in various biomaterials demonstrated that only the first term in this series equation is of consequence, which yields the following relationship (Garbado, Rech, & Ayub, 2011): ln…”
Section: Application Of Fickian Diffusion To the Whey Protein E Nicotmentioning
confidence: 99%
“…Earlier work in various biomaterials demonstrated that only the first term in this series equation is of consequence, which yields the following relationship (Garbado, Rech, & Ayub, 2011): ln…”
Section: Application Of Fickian Diffusion To the Whey Protein E Nicotmentioning
confidence: 99%
“…Por outro lado, os resultados apresentados por Florêncio et al (2013) obtiveram, com A adição de sacarose é necessária, haja vista que a levedura Saccharomyces cerevisiae não utiliza a lactose presente no meio, mas utiliza açúcares fermentescíveis (glicose e frutose), que são produtos da hidrólise da sacarose no processo de fermentação alcoólica (Gabardo et al, 2011). Nesse caso, o soro foi usado como fonte de nutrientes (sais, nitrogenados, etc.)…”
Section: Produção De Etanol a Partir Do Soro De Leiteunclassified
“…The concentration of suspended cells was determined by absorbance at 600 nm and correlated with dry cell weight (g L −1 ). The concentration of cells in the alginate spheres was analyzed dissolving five beads with a diameter of 3.8 mm into 10 mL of sodium citrate buffer 0.1 M (pH 6.2) and vortex stirred by 15 min to accelerate their breakup [12].…”
Section: Analytical Determinationsmentioning
confidence: 99%